Lithuanian Rural Settlements: The Legacy of Soviet Rural Planning and Current Challenges - KRIAUČIŪNAS EDIS; BURNEIKA DONATAS; UBAREVIČIENĖ RŪTA; BARANAUSKIENĖ VIKTORIJA (Quaestiones Geographicae, 2025)
The article analyses the changes to the system of the distribution of population in rural areas in Lithuania, one of the former Soviet states: it compares the transformation of settlements during the socialist era and the transformations of the rural settlement system after 1990. The aim of this paper is to analyse the results of the Soviet rural settlement planning policy and to evaluate post-Soviet rural development trajectories in Lithuania. Despite different political and economic systems, depopulation was the most important demographical trend in Lithuanian rural areas from the second half of the 20th century. The transformation of rural settlements after the collapse of the Soviet system has been quite chaotic and difficult to control. In the 21st century, both the shrinking periphery and the newly expanding settlements lack the infrastructure of public services.